Perancangan Video Promosi Objek Wisata Ranudi Kabupaten Probolinggo Jawa Timur - Riyanti Suci Purwasi; Faldi Hendrawan; Ahmad Zakiy Ramadhan (Jurnal Desain Komunikasi Visual Asia, 2018)
The rapid advances in information technology (IT) provide ease in accessing and presenting information in various forms and media, in general (books, brochures, magazines, tabloids and posters), as well as in electronic or digital format (internet, film, cd-interactive And games). With the availability of many presentations the results of research data can be presented with more interesting and easy to use then the results data is used, such as contains elements of information This media is a promotion video about Ranu Tourism in object Probolinggo District-East Java. The video provides info on Ranu tourism in Probolinggo District-East Java. This promotional media will be presented in the form of promotion videos and information that will make it easier for tourists to know about WIsata Ranu in Probolinggo-East Java regency it aims to captivate the attractiveness of the tourists both local and foreign tourists to come and know the have tour Probolinggo. MPEG (MotionPicture Expert Group) was chosen because it has several adventages, Including MPEG is an international standard for digital audio and video format, typically used for VCD and DVD. In creating a video as an attractive media campaign, the media is created with elements such as videography, storyline, storyboard, and audio concepts. Software support in the post-production stage is Adobe After Effect to create an opening, Adobe Photoshop to design information, and Adobe Premiere Pro is used for video editing process. From the results of the respondents, the percentage value of the community responded well to the resulting product, so that the final study of 97% said that this video attracted their attention and deserved to be the Promotion Media Ranu Tourism object in Probolinggo District.